Two new species of Leporinus Agassiz, 1929 (Characiformes: Anostomidae) from tributaries of the lower Amazon basin in Brazil - Birindelli, José L. O.; Teixeira, Tulio F.; Britski, Heraldo A. (Zootaxa, 2016)
Two new species of Leporinus (Characiformes, Anostomidae) are described. Both new species are diagnosed by having one dark blotch on midline of anterior portion of the flank (between opercle and pelvic-fin origin) surrounded by five to seven dark blotches; and a subinferior mouth with three premaxillary teeth. Leporinus multimaculatus, new species, is distributed in small and medium-sized tributaries of the rio Tocantins and rio Xingu basins, and also in the rio Jari and coastal drainages of Amapá state, whereas L. torrenticola, new species, is endemic to the rapids of the rio Xingu and its main tributaries. The number of scale rows around the caudal peduncle is the main feature distinguishing L. multimaculatus from L. torrenticola. Comments on the diagnostic features of the newly described species are provided. In addition, the phylogenetic position and generic assignment of the new species are discussed based on available information from recent morphological and molecular analyses.